Porous sodium solid electrolyte powder as well as preparation method and application thereof

By forming a porous sodium solid electrolyte powder coating on the polymer separator of the sodium ion battery, the wetting ability of the electrolyte is improved, the problem of insufficient low-temperature performance of sodium ion battery is solved, and the conductivity and cycle life of the battery are significantly improved.

CN119315096APending Publication Date: 2025-01-14LIONGO (CHANGZHOU) NEW ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411505759.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The low-temperature performance of sodium ion batteries is insufficient, mainly due to the poor wetting of polyethylene or polypropylene separators on the electrolyte, which slows down the transmission rate of the electrolyte at low temperatures, affecting the battery performance.

Method used

Using porous sodium solid electrolyte powder Na-β''-Al2O3, the coating is formed with the surface of the polymer membrane to improve the wetting properties of the electrolyte on the membrane, including mixing the aluminum source with sodium carbonate in a heat-resistant and high-thermal conductivity container. The pore size and porosity are controlled to form a pore sodium solid electrolyte powder with a pore size of 5nm~100nm and a porosity of 50%~70%, and mixed with a binder and wetting agent to form a coating layer.

Benefits of technology

It significantly improves the ionic conductivity, first-circle coulomb effect, rate performance and low-temperature performance of sodium ion batteries, reduces the contact angle of the diaphragm, and extends the cycle life of the battery at low temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119315096A_ABST
    Figure CN119315096A_ABST
Patent Text Reader

Abstract

The invention provides porous sodium solid electrolyte powder, the pore diameter of which is 5-100 nm and the porosity of which is 50-70%. The invention also provides a preparation method of the porous sodium solid electrolyte powder, a diaphragm containing the porous sodium solid electrolyte powder and a sodium ion battery containing the diaphragm. The porous sodium solid electrolyte powder provided by the invention has rich pores, and after a coating layer is formed on the surface of a polymer diaphragm, the wettability of a sodium-ion battery electrolyte to the diaphragm can be remarkably improved, so that the ionic conductivity, the first-circle coulombic efficiency, the rate capability and the low-temperature performance of the sodium-ion battery are improved. Experimental results show that compared with a coating layer formed by dense Na-beta ''-Al2O3 powder on the diaphragm, the contact angle of the diaphragm is reduced to be less than 22 degrees, and the number of turns is increased to be more than 850 when the capacity of the sodium-ion battery is reduced to 85% at the temperature of 0 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ion batteries, and in particular to a porous sodium solid electrolyte powder, a preparation method thereof and an application thereof. Background Art

[0002] Compared with lithium-ion batteries, sodium-ion batteries have relatively higher power density and better low-temperature performance. However, the performance of these properties requires good wettability of the electrolyte to the separator.

[0003] The polyethylene (PE) or polypropylene (PP) diaphragms usually used in sodium-ion batteries have a large contact angle with the electrolyte and exhibit extremely poor wettability. Therefore, current commercial battery cells generally use PE or PP diaphragms coated with alumina coatings, and the electrolyte exhibits significantly improved wettability on them. However, the low-temperature performance of the sodium-ion batteries assembled from them needs to be further improved. Summary of the invention

[0004] In view of this, the present invention provides a porous sodium solid electrolyte powder, a preparation method and an application thereof. The porous sodium solid electrolyte powder provided in the present application forms a coating on the surface of a polymer membrane, which can improve the wettability of the electrolyte to the membrane, thereby improving the low-temperature performance of a sodium ion battery.

[0005] The present application provides a porous sodium solid electrolyte powder, which is Na-β''-Al2O3, with a pore size of 5nm~100nm and a porosity of 50%~70%.

[0006] The present application also provides a method for preparing a porous sodium solid electrolyte powder, comprising the following steps:

[0007] Mixing an aluminum source with sodium carbonate to obtain a powder; the aluminum source is selected from boehmite, α-Al2O3 or diaspore;

[0008] The powder is placed in a heat-resistant and high-thermal-conductivity container for calcination to obtain a porous sodium solid electrolyte powder;

[0009] The thickness of the powder in the heat-resistant and highly thermally conductive container is 10-15 cm, the calcination temperature is 1250° C.-1300° C., and the calcination time is 1 h-1.5 h.

[0010] In some specific implementations, the heating rate of the calcination is 5°C / min to 8°C / min.

[0011] In some specific implementations, the mass ratio of the aluminum source to sodium carbonate is 6.5-7:1.

[0012] In some specific implementations, the heat-resistant and high thermal conductivity container is an alumina calcining sagger.

[0013] The present application provides a diaphragm, comprising a polymer diaphragm and a coating layer formed on at least one surface of the polymer diaphragm, wherein the coating layer comprises the porous sodium solid electrolyte powder described in the above technical solution or the porous sodium solid electrolyte powder prepared according to the method described in the above technical solution.

[0014] In some specific implementations, the particle size of the porous sodium solid electrolyte powder is 400nm~600nm.

[0015] In some specific implementations, the coating layer further includes a binder and a wetting agent.

[0016] In some specific implementations, the binder is selected from at least one of carboxymethyl acrylate, polyvinylidene fluoride and its derivatives, carboxymethyl cellulose salt and polyacrylate;

[0017] The wetting agent is selected from at least one of sodium lauryl sulfate and a condensate of fatty alcohol and ethylene oxide.

[0018] The present application also provides a sodium ion battery, comprising the diaphragm described in the above technical solution.

[0019] The present application provides a porous sodium solid electrolyte powder, which is Na-β''-Al2O3, with abundant pores. After forming a coating layer on the surface of a polymer diaphragm, the wettability of the sodium ion battery electrolyte to the diaphragm can be significantly improved, thereby improving the ionic conductivity, first-cycle coulomb efficiency, rate performance and low-temperature performance of the sodium ion battery. The experimental results show that compared with dense Na-β''-Al2O3 powder and then forming a coating layer on the diaphragm, the contact angle of the diaphragm is reduced to below 22°, and the number of cycles when the sodium ion battery capacity drops to 85% at 0°C is increased to more than 850 cycles. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a SEM photo of the porous powder prepared in Example 1 of the present application;

[0021] Figure 2 This is a SEM photo of the powder prepared in Comparative Example 1 of the present application;

[0022] Figure 3 This is a SEM photograph of the powder prepared in Comparative Example 2 of the present application. DETAILED DESCRIPTION

[0023] It should be understood that the expression "one or more of..." includes each of the items recited after the expression individually and in various different combinations of two or more of the recited items, unless otherwise understood from the context and usage. The expression "and / or" in combination with three or more recited items should be understood to have the same meaning, unless otherwise understood from the context.

[0024] The use of the terms "comprising", "having" or "containing", including their grammatical synonyms, should generally be understood as open and non-restrictive, for example not excluding other unrecited elements or steps, unless otherwise specifically stated or otherwise understood from the context.

[0025] It should be understood that the order of steps or the order in which certain actions are performed is not important as long as the present invention remains operable. In addition, two or more steps or actions may be performed simultaneously.

[0026] The use of any and all examples or exemplary language, such as "for example" or "including", herein is intended only to better illustrate the invention and does not limit the scope of the invention unless otherwise claimed. No language in this specification should be construed as indicating that any non-claimed element is essential to the practice of the invention.

[0027] In addition, the numerical ranges and parameters used to define the present invention are approximate values, and the relevant values ​​in the specific embodiments have been presented as accurately as possible. However, any numerical value inherently inevitably contains standard deviations due to individual test methods. Therefore, unless otherwise expressly stated, it should be understood that all ranges, quantities, values ​​and percentages used in this disclosure are modified by "about". Here, "about" generally means that the actual value is within plus or minus 10%, 5%, 1% or 0.5% of a specific value or range.

[0028] The present application provides a porous sodium solid electrolyte powder, which is Na-β''-Al2O3, with a pore size of 5nm~100nm, preferably 6nm~50nm, more preferably 7nm~20nm, and most preferably 10nm~15nm; the porosity is 50%~70%, preferably 52%~68%, and more preferably 55%~65%.

[0029] The present application also provides a method for preparing a porous sodium solid electrolyte powder, comprising the following steps:

[0030] Mixing an aluminum source with sodium carbonate to obtain a powder; the aluminum source is selected from boehmite, α-Al2O3 or diaspore;

[0031] The powder is placed in a heat-resistant and high-thermal-conductivity container for calcination to obtain a porous sodium solid electrolyte powder;

[0032] The thickness of the powder in the heat-resistant and highly thermally conductive container is 10-15 cm, the calcination temperature is 1250° C.-1300° C., and the calcination time is 1 h-1.5 h.

[0033] The present application uses boehmite, α-Al2O3 or diaspore and sodium carbonate as raw materials, first mixes them evenly, and then calcines them at a temperature of 1250°C~1300°C for 1h~1.5h in a heat-resistant and highly thermally conductive container with a thickness of 10cm~15cm to obtain a porous sodium solid electrolyte powder.

[0034] In some specific implementations, the aluminum source is boehmite. During the calcination process, the boehmite is gradually dehydrated to generate δ-Al2O3 and α-Al2O3, while sodium ions enter the lattice of alumina to generate Na-β''-Al2O3.

[0035] Boehmite is a dense crystal. During the calcination and dehydration process, the local structure of boehmite collapses to form pores. However, at the calcination temperature, the crystal growth rate is fast, and the pores are easily closed to form a dense powder. Therefore, the calcination time needs to be reduced. However, reducing the calcination time will lead to insufficient reaction. The present application improves the uniformity of the mixture by dry mixing, and optimizes the powder loading (i.e., the thickness in the container) to ensure sufficient reaction and retain the pores.

[0036] The present application has no special restrictions on the sources of boehmite and sodium carbonate, and they can be purchased on the market. The present application first mixes boehmite and sodium carbonate, preferably dry mixing in a dry mixer, and uniform mixing is conducive to the formation of porous powder. In some specific implementations, the mass ratio of the boehmite and sodium carbonate is 6.5~7:1, for example, it can be 6.5:1, 6.8:1, 7:1, or any value between 6.5~7:1. In some specific implementations, the mixing speed is 100rpm~500rpm, preferably 150rpm~450rpm, and more preferably 200rpm~400rpm.

[0037] After uniform mixing, the obtained powder is loaded into a heat-resistant high thermal conductivity container for calcination to obtain a porous sodium solid electrolyte powder. Specifically, the present application loads the obtained powder into a heat-resistant high thermal conductivity container and calcines it in a muffle furnace, and obtains a porous powder by controlling the charge amount, calcination temperature and calcination time. In some specific implementations, the heat-resistant high thermal conductivity container includes but is not limited to alumina calcination sagger, and the thickness of the powder in the container is 10cm~15cm, preferably 12cm~14cm, for example, it can be 10cm, 11cm, 12cm, 13cm, 14cm or 15cm, or any value between 10cm~15cm. In the present application, the raw material powder and the product powder are both poor conductors of heat, and the reaction will also absorb a lot of heat. If the charge amount is too much, the internal reaction will be incomplete; if the charge amount is too small, the reaction is too fast, and the remaining heating time will increase the crystallinity of the powder, increasing the difficulty of controlling the reaction temperature.

[0038] In some specific implementations, the heating rate of the calcination is 5°C / min~8°C / min, preferably 6°C / min~7°C / min, for example, 5°C / min, 6°C / min, 7°C / min or 8°C / min, or any value between 5°C / min~8°C / min. A relatively high heating rate is conducive to the maintenance of powder pores. In some specific implementations, the calcination temperature is 1250°C~1300°C, preferably 1270°C~1300°C, for example, 1250°C, 1260°C, 1270°C, 1280°C, 1290°C, 1300°C, or any value between 1250°C~1300°C. In some specific implementations, the calcination time is 1h~1.5h, for example, 1h, 1.1h, 1.2h, 1.3h, 1.4h or 1.5h, or any value between 1h~1.5h.

[0039] After calcination, a porous sodium solid electrolyte powder can be obtained, which is Na-β''-Al2O3. In some specific implementations, the step of crushing the obtained porous sodium solid electrolyte powder is also included, preferably crushing the porous sodium solid electrolyte powder to a D50 value of 400nm~600nm, more preferably 450nm~550nm. In some specific implementations, the crushing is carried out in a sand mill, and the speed of the crushing is preferably 1000rpm~2500rpm, more preferably 1500rpm~2000rpm, and most preferably 1700rpm~1900rpm, for example, it can be 1700rpm, 1800rpm or 1900rpm, or it can be any value between 1000rpm~2500rpm.

[0040] The present invention also provides a diaphragm, comprising a polymer diaphragm and a coating layer formed on at least one surface of the polymer diaphragm, wherein the coating layer comprises the porous sodium solid electrolyte powder described in the above technical solution or the porous sodium solid electrolyte powder prepared according to the method described in the above technical solution.

[0041] The present application has no special limitation on the polymer membrane, which may be a polypropylene (PP) microporous membrane or a polyethylene (PE) microporous membrane, etc.

[0042] The coating layer is formed on at least one surface of the polymer isolation membrane. It can be formed on one surface, ie, single-sided coating, or on two opposite surfaces, ie, double-sided coating, which will not be described in detail in this application.

[0043] In some specific implementations, the coating layer includes the porous sodium solid electrolyte powder described in the above technical solution. In some specific implementations, the porous sodium solid electrolyte powder is Na-β''-Al2O3, and the particle size (D50 value) is 400nm~600nm, more preferably 450nm~550nm.

[0044] In some specific implementations, the coating layer further includes a binder and a wetting agent. The binder is used to form the coating layer and increase the adhesion of the coating layer. In some specific implementations, the binder includes but is not limited to at least one of carboxymethyl acrylate, polyvinylidene fluoride and its derivatives, carboxymethyl cellulose salt and polyacrylate, preferably carboxymethyl acrylate. The wetting agent is used to increase the wettability of the diaphragm. In some specific implementations, the wetting agent includes but is not limited to at least one of sodium lauryl sulfate and a condensate of a fatty alcohol and ethylene oxide, preferably sodium lauryl sulfate.

[0045] In some specific implementations, the mass ratio of the porous sodium solid electrolyte powder, the binder and the wetting agent is 30~40:1~2:0.1~2, preferably 30~40:1.3~1.8:0.5~1.5.

[0046] In some specific implementations, the thickness of the coating layer is preferably 1 μm to 3 μm, more preferably 1.5 μm to 2.5 μm, and most preferably 2 μm.

[0047] The present application has no particular limitation on the preparation method of the diaphragm, and the diaphragm can be prepared according to the following method:

[0048] A slurry containing porous sodium solid electrolyte powder, a binder and a wetting agent is coated on at least one surface of a polymer diaphragm to obtain the diaphragm.

[0049] Specifically, the present application first crushes the porous sodium solid electrolyte powder obtained, preferably crushing the porous sodium solid electrolyte powder to a D50 value of 400nm~600nm, more preferably 450nm~550nm. In some specific implementations, the crushing is carried out in a sand mill, and the speed of the crushing is preferably 1000rpm~2500rpm, more preferably 1500rpm~2000rpm, and most preferably 1700rpm~1900rpm, for example, 1700rpm, 1800rpm or 1900rpm, or any value between 1000rpm~2500rpm. The solid content of the slurry obtained after crushing is preferably 30wt%~40wt%.

[0050] After the slurry is obtained, it is mixed with a binder and a wetting agent, and coated on the polymer membrane to form a coating layer. In some specific embodiments, the coating is preferably roller coating.

[0051] The present application also provides a sodium ion battery, comprising the diaphragm described in the above technical solution. Specifically, the sodium ion battery provided by the present application comprises a positive electrode sheet, a negative electrode sheet, a diaphragm described in the above technical solution for separating the positive electrode sheet and the negative electrode sheet, and an electrolyte.

[0052] The sodium ion battery includes a positive electrode sheet, and the positive electrode sheet includes a positive current collector and a positive active material layer formed on the positive current collector. In some specific implementations, the positive current collector can be a metal foil, including but not limited to aluminum foil, nickel foil, stainless steel, etc. For example, the positive current collector can be aluminum foil. A positive active material layer is provided on the surface of the positive current collector, which includes a positive electrode material, an optional conductive agent, and an optional binder. In some specific implementations, the mass ratio of the positive electrode material, the conductive agent, and the binder is 90~98:1~5:1~5, preferably 92~95:2~4:1.5~2. In some specific implementations, the positive electrode material includes but is not limited to Na3V2(PO4)3, Na2Ni[Fe(CN)6], Na2MnO4, etc., and can be one or more thereof. When the positive electrode material is a mixture of multiple specific substances, the present application does not make too many restrictions on the ratio between the specific substances. In some specific implementations, the conductive agent includes but is not limited to carbon black, hard carbon, graphite, carbon nanotubes, graphene, etc., and can be one or more thereof. When the conductive agent is a mixture of multiple specific substances, the present application does not make too many restrictions on the ratio between the specific substances. The binder includes but is not limited to polyvinylidene fluoride, polytetrafluoroethylene, polyacrylic acid, polyamide, lithium polyacrylate, methacrylate, sodium polymethylcellulose, aluminum dihydrogen phosphate, etc., and can be one or more thereof. When the binder is a mixture of multiple specific substances, the present application does not make too many restrictions on the ratio between the specific substances.

[0053] The present application has no special restrictions on the preparation method of the positive electrode sheet. The positive electrode material, the optional conductive agent and the optional binder are uniformly mixed in a solvent, such as N-methylpyrrolidone (NMP), coated on the positive electrode current collector in an optional manner, and dried to obtain the positive electrode sheet. Furthermore, after drying, rolling, slicing, etc. are also included, and the present application has no special restrictions on them.

[0054] The sodium ion battery includes a negative electrode sheet, and the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer formed on the negative electrode current collector. In some specific implementations, the negative electrode current collector can be a metal foil, including but not limited to aluminum foil, nickel foil, stainless steel, etc. For example, the negative electrode current collector can be aluminum foil. A negative electrode active material layer is provided on the surface of the negative electrode current collector, which includes a negative electrode material, an optional conductive agent, an optional binder, and an optional thickener. In some specific implementations, the mass ratio of the negative electrode material, the conductive agent, the binder, and the thickener is 90~98:0.5~2:0.5~3:1~5, preferably 92~97:0.7~1.5:0.8~1.5:1~2. In some specific implementations, the negative electrode material includes but is not limited to hard carbon, carbon black, soft carbon, graphene, and can be one or more thereof. When the negative electrode material is a mixture of multiple specific substances, the present application does not make too many restrictions on the ratio between the specific substances. In some specific implementations, the conductive agent includes but is not limited to carbon black, hard carbon, graphite, carbon nanotubes, graphene, etc., and can be one or more of them. When the conductive agent is a mixture of multiple specific substances, the present application does not make too many restrictions on the ratio between the specific substances. The binder includes but is not limited to styrene-butadiene rubber (SBR), polytetrafluoroethylene (PTFE), water-based polyacrylate (PAA), etc., and can be one or more of them. When the binder is a mixture of multiple specific substances, the present application does not make too many restrictions on the ratio between the specific substances. The thickener includes but is not limited to sodium carboxymethyl cellulose (CMC), methyl cellulose (MC), ethyl cellulose (EC), hydroxyethyl cellulose (HEC), hydroxypropyl methyl cellulose (HPMC), etc., and can be one or more of them. When the thickener is a mixture of multiple specific substances, the present application does not make too many restrictions on the ratio between the specific substances.

[0055] The present application has no special restrictions on the preparation method of the negative electrode sheet. The negative electrode material, the optional conductive agent, the optional binder and the optional thickener are uniformly mixed in a solvent, such as deionized water, and coated on the negative electrode current collector in an optional manner, and then dried to obtain the negative electrode sheet. Furthermore, after drying, rolling, slicing, etc. are also included, and the present application has no special restrictions on them.

[0056] The sodium ion battery adopts the diaphragm described in the above technical solution, the porous sodium solid electrolyte, especially the slight reaction of Na-β''-Al2O3 powder with the organic solvent in the electrolyte will enhance the wettability of the electrolyte to the coated diaphragm. On the other hand, the coating material is a porous powder, and the micropores thereon can further enhance the wettability of the electrolyte through capillary action. At the same time, the capillary action can also accelerate the transport of sodium ions in the electrolyte by enhancing convection in local areas of the electrolyte, which is very beneficial to improving the low-temperature performance of the battery, because one of the main reasons for the insufficient low-temperature performance is that the sodium ion transmission rate at low temperature is slowed down, resulting in incomplete electrode reaction. The porous powder coating can accelerate the transport of sodium ions by enhancing convection.

[0057] In some specific implementations, the electrolyte may include a sodium salt, an organic solvent, and an additive, wherein the sodium salt includes but is not limited to sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium perchlorate (NaClO4), sodium hexafluoroarsenate (NaAsF6), sodium bis(fluorosulfonyl)imide (NaFSI), sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), sodium trifluoromethanesulfonate (NaTFS), sodium difluorooxalatoborate (NaDFOB), sodium dioxalatoborate (NaBOB), sodium difluorophosphate (NaPO2F2 ), one or more of sodium difluorobis(oxalate)phosphate (NaDFOP) and sodium tetrafluorooxalate)phosphate (NaTFOP), preferably sodium hexafluorophosphate; the organic solvent includes but is not limited to ethylene carbonate, dimethyl carbonate, diethyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, ethylene carbonate, ethyl propionate, ethyl acetate, methyl acetate, dimethyl acetate, methyl butyrate, and n-propyl acetate, preferably a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC), wherein the volume ratio of EC to DEC is 1~2:1~2, more preferably 1:1; the additive includes but is not limited to one or more of vinylene carbonate, fluoroethylene carbonate, 1,3-propane sultone, vinyl sulfate, diphenyl carbonate, toluene carbonate, acrylic nitrile, succinic anhydride, succinonitrile, and adiponitrile.

[0058] In some specific implementations, in the electrolyte, the electrolyte is sodium hexafluorophosphate, the solvent is a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC), the volume ratio of ethylene carbonate (EC) to diethyl carbonate (DEC) is preferably 1~2:1~2, more preferably 1:1, and the concentration of the electrolyte is 0.5 mol / L~2 mol / L, preferably 0.8 mol / L ~1.5 mol / L.

[0059] In the present application, a positive electrode sheet, a separator and a negative electrode sheet are stacked in sequence to obtain a battery cell assembly, which is sealed in an aluminum-plastic bag, and an electrolyte is injected. After packaging, standing, formation and other processes, a sodium ion battery is obtained.

[0060] After obtaining the sodium ion battery, its performance was tested and it showed good ionic conductivity, first-cycle coulombic efficiency, rate performance and low-temperature performance.

[0061] The porous sodium solid electrolyte powder, its preparation method and its application provided by the present application are further described below in conjunction with the embodiments.

[0062] Example 1

[0063] 1.1 Synthesis of porous Na-β''-Al2O3 powder

[0064] Boehmite and sodium carbonate were placed in a VC dry mixer at a mass ratio of 6.5:1, and 0.5 wt% of carbon powder accounting for the total mass of boehmite and sodium carbonate was added as a lubricant. The rotation speed was adjusted to 350 rpm and the mixing time was 30 min.

[0065] The mixed powder was loaded into a special sagger for alumina calcination. The thickness of the loaded powder was controlled to be 10 cm. The powder was placed in a muffle furnace for high-temperature reaction. The heating rate was 5 °C / min. The reaction temperature was controlled to be 1270 °C and kept warm for 1 hour to obtain porous Na-β''-Al2O3 powder.

[0066] The porous Na-β''-Al2O3 powder was characterized, and the results are shown in Figure 1 , Figure 1 This is a SEM photo of the porous powder prepared in Example 1 of the present application. Figure 1 It can be seen that the pore diameter of the porous powder is 10.9888 nm and the porosity is 59.6%.

[0067] 1.2 Slurry preparation and diaphragm coating

[0068] The synthesized Na-β''-Al2O3 powder was crushed by a sand mill at a speed of 1800 rpm until D50 dropped to 400-600 nm and the solid content of the slurry was 30-40wt%. A binder (carboxymethyl acrylate) and a wetting agent (sodium dodecyl sulfate) were added to the sand-milled slurry in sequence, wherein the binder content was 4.5% of the solid mass in the slurry and the wetting agent was 0.7% of the total mass of the slurry. After mixing evenly, the slurry was coated on the PE base film by roller coating, and the coating thickness was controlled to be 2 μm. Double-sided coating was performed to obtain a diaphragm.

[0069] 1.3 Preparation of sodium ion soft pack batteries

[0070] The positive electrode active material Na3V2(PO4)3, the conductive agent Super P, and the binder PVDF are added to N-methyl-2-pyrrolidone (NMP) in a weight ratio of 95: 2.2: 1.8 to prepare a slurry. The positive electrode slurry is evenly coated on the two surfaces of the aluminum foil current collector, and further dried, rolled, and cut to obtain the positive electrode sheets.

[0071] The negative electrode active material hard carbon, the conductive agent carbon black, the binder styrene-butadiene rubber (SBR), and the thickener sodium hydroxymethyl cellulose (CMC) are dissolved in deionized water at a weight ratio of 96.0:0.9:0.9:1.2 to prepare a negative electrode slurry; the negative electrode slurry is evenly coated on the two surfaces of the aluminum foil current collector, and the negative electrode sheets are obtained after drying, rolling, and slitting.

[0072] In the dry room, the positive electrode plates, separators and negative electrode plates are dried and stacked in order to obtain battery cell components, which are then sealed in aluminum-plastic bags and injected with electrolyte. After packaging, standing and forming processes, soft-pack batteries are obtained. The rated capacity of the soft-pack batteries is 1Ah and the injection volume is 3g. The electrolyte used is 1M NaPF6, and the solvent is ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 1:1.

[0073] To ensure the credibility of the results, three cells were assembled in parallel and numbered as Examples 1.1 to 1.3.

[0074] Embodiment 2~4

[0075] The difference from Example 1 is that the PE base film is coated with Na-β''-Al2O3 powder prepared according to the following method, and three battery cells are assembled in parallel:

[0076]

[0077] The thickness refers to the thickness of the powder loaded into the special sagger for calcining alumina.

[0078] Comparative Example 1

[0079] The difference from Example 1 is that the PE base film is coated with well-crystallized dense α-Al2O3 powder purchased from Yishitong, and three battery cells are assembled in parallel, numbered as Comparative Examples 1.1 to 1.3. Figure 2 , Figure 2 This is the SEM photo of the powder used in Comparative Example 1 of this application. Figure 2 It can be seen that the powder is a dense powder.

[0080] Comparative Example 2

[0081] The difference from Example 1 is that the PE base film is coated with Na-β''-Al2O3 powder prepared according to the following method, and three battery cells are assembled in parallel, which are numbered as Comparative Examples 2.1 to 2.3:

[0082] The powder synthesis method is as follows:

[0083] Boehmite and sodium carbonate were placed in a VC dry mixer at a ratio of 6.5:1, and 0.5 wt% of the total mass of boehmite and sodium carbonate was added as carbon powder as a lubricant. The rotation speed was adjusted to 350 rpm and the mixing time was 30 min.

[0084] The mixed powder was loaded into a special sagger for alumina calcination. The thickness of the loaded powder was controlled to be 10 cm. The powder was placed in a muffle furnace for high-temperature reaction. The heating rate was 5°C / min. The reaction temperature was controlled to be 1300°C and kept warm for 4 hours to obtain Na-β''-Al2O3 powder.

[0085] The porous Na-β''-Al2O3 powder was characterized, and the results are shown in Figure 3 , Figure 3 This is a SEM photo of the powder prepared in Comparative Example 2 of this application. Figure 3 It can be seen that by increasing the reaction temperature and prolonging the reaction time, the obtained powder is a dense powder.

[0086] Comparative Example 3

[0087] The difference from Example 1 is that the PE base film is coated with Na-β''-Al2O3 powder prepared according to the following method, and three battery cells are assembled in parallel, which are numbered as Comparative Examples 3.1 to 3.3:

[0088] The powder synthesis method is as follows:

[0089] Boehmite and sodium carbonate were placed in a VC dry mixer at a ratio of 6.5:1, and 0.5 wt% of the total mass of boehmite and sodium carbonate was added as carbon powder as a lubricant. The rotation speed was adjusted to 350 rpm and the mixing time was 30 min.

[0090] The mixed powder was loaded into a special sagger for alumina calcination. The thickness of the loaded powder was controlled to be 5 cm. The powder was placed in a muffle furnace for high-temperature reaction. The heating rate was 5 °C / min. The reaction temperature was controlled to be 1270 °C and kept warm for 1 hour to obtain Na-β''-Al2O3 powder.

[0091] The powder thickness is too small and the obtained powder is dense powder.

[0092] Comparative Example 4

[0093] The difference from Example 1 is that the PE base film is coated with Na-β''-Al2O3 powder prepared according to the following method, and three battery cells are assembled in parallel, which are numbered as Comparative Examples 4.1 to 4.3:

[0094] The powder synthesis method is as follows:

[0095] Boehmite and sodium carbonate were placed in a VC dry mixer at a ratio of 6.5:1, and 0.5 wt% of the total mass of boehmite and sodium carbonate was added as carbon powder as a lubricant. The rotation speed was adjusted to 350 rpm and the mixing time was 30 min.

[0096] The mixed powder was loaded into a special sagger for alumina calcination. The thickness of the loaded powder was controlled at 20 cm. The powder was placed in a muffle furnace for high-temperature reaction. The heating rate was 5 ° C / min. The reaction temperature was controlled at 1300 ° C and kept warm for 4 hours to obtain Na-β''-Al2O3 powder.

[0097] The powder thickness is too large, the reaction temperature is high, and the reaction time is long, so the obtained powder is a dense powder.

[0098] Comparative Example 5

[0099] The difference from Example 1 is that a PE base film is coated with a well-crystallized non-porous NZSP powder prepared according to the following method, and three battery cells are assembled in parallel, which are numbered as Comparative Examples 5.1 to 5.3:

[0100] The powder synthesis method is as follows:

[0101] Sodium carbonate: zirconium oxide: silicon oxide: ammonium dihydrogen phosphate was added into a VC dry mixer in a ratio of 263 g: 370 g: 207 g: 191 g, and carbon powder accounting for 0.5 wt% of the total mass of sodium carbonate, zirconium oxide, silicon oxide and ammonium dihydrogen phosphate was added as a lubricant. The rotation speed was adjusted to 350 rpm and the mixing time was 30 min.

[0102] The mixed powder was loaded into a special sagger for alumina calcination with a thickness of 20 cm, and placed in a muffle furnace for high-temperature reaction. The heating rate was 5 ° C / min, and the reaction temperature was controlled to be 1200 ° C. The temperature was kept for 12 hours to obtain a well-crystallized non-porous sodium zirconium silicon phosphorus (NZSP) powder with a molecular formula of Na 1+x Zr2Si x P 3-x O 12 (0≤x≤3).

[0103] Test example

[0104] The performance of the diaphragms and cells prepared in the examples and comparative examples was tested in the following manner:

[0105] (1) Diaphragm wettability test

[0106] According to the standard GB / T 30447-2013, the temperature and humidity during the test were 22.5℃ / 30%RH, and the electrolyte used was 1M NaPF6 dissolved in EC:EMC=1:1 (vol%).

[0107] 2. Ionic conductivity test of diaphragm

[0108] The dried diaphragm was cut into 16 mm diameter diaphragm discs using a punching machine, and assembled into a stainless steel ion blocking electrode symmetrical battery in the order of positive electrode shell, stainless steel gasket, diaphragm, stainless steel gasket, spring, and negative electrode shell in an argon-filled glove box. The electrolyte used was 1 mol / L NaPF6 EC / EMC solution. 40 μL of electrolyte was dripped on both sides of the diaphragm and fully soaked for 12 hours. The whole process was carried out in a dry room with a dew point of -40 ° C. The thickness D and cross-sectional area S of the diaphragm were measured with a vernier caliper, and its AC impedance R was measured. The ionic conductivity (S / cm) was calculated according to the formula σ=D / SR.

[0109] 3. Coulomb efficiency test

[0110] Place the sodium ion battery in a constant temperature environment of 25℃ for 3h, keep the temperature inside and outside the battery stable, charge it to 3.8V at a constant current and voltage of 0.1C (1C=117.6mAh / g), and discharge it to 2V at a constant current of 0.1C to test the coulombic efficiency. Coulombic efficiency = first cycle discharge specific capacity / first cycle charge specific capacity*100%.

[0111] 4. Low temperature performance test method of battery cells

[0112] The prepared battery cell was placed in a constant temperature box at 0°C, charged to 3.8V at a constant current of 1C, then charged at a constant voltage of 3.8V until the current dropped to 0.05C, left for 10 minutes, and then discharged to 2V at 1C. The measured discharge capacity was recorded as the initial capacity C1. Repeat the above cycle steps for the same battery, and record the number of cycles when the capacity dropped to 85% of the C1 capacity.

[0113] Other test items are tested according to general methods.

[0114] The results are shown in Table 1, which shows the performance of the diaphragms and cells prepared in the examples and comparative examples of the present application.

[0115] Table 1 shows the performance of the diaphragms and cells prepared in the examples and comparative examples of the present application.

[0116]

[0117]

[0118] It can be seen from Table 1 that compared with Comparative Example 1, the solid electrolyte coated diaphragms used in Example 1 and Comparative Examples 2-3 exhibit smaller contact angles, proving that the slight side reaction between the solid electrolyte and the electrolyte helps to improve wettability, and this enhanced wettability also makes the battery have a longer cycle life at low temperatures.

[0119] Comparative Examples 2 and 3 synthesized dense Na-β''-Al2O3 by adjusting the calcination temperature, time and the amount of material in the sagger. Figure 2 As shown, it shows that the synthesis of porous Na-β''-Al2O3 requires precise control of the synthesis conditions. Compared with the dense Na-β''-Al2O3 coated membrane used in Comparative Example 2, the membrane coated with porous Na-β''-Al2O3 in Example 1 exhibits a smaller contact angle and a significantly extended cycle life at low temperatures, indicating that the porous particles can further enhance the wettability of the electrolyte to the membrane through capillary action. The improvement of wettability is of great significance for maintaining the stable cycle of the battery at low temperatures.

[0120] Compared with Example 1, Comparative Example 4 uses a larger charging amount, and the reaction is incomplete. XRD test shows that only the powder in the surface area completes the full reaction, and the internal reaction product is mainly δ-Al2O3, which has a large contact angle and a poor cycle life at low temperatures.

[0121] Comparative Example 5 uses a dense NZSP solid electrolyte to coat the diaphragm, and its effect is close to that of dense Na-β''-Al2O3, with a larger contact angle and a poor cycle life at low temperatures.

[0122] Compared with comparative examples 1 to 5, the charge thickness, holding time and temperature of Examples 1 to 4 have a greater influence on the morphology of Na-β''-Al2O3. In the examples in which a single variable is controlled to change within a certain range, the batteries coated with the diaphragm and assembled with the diaphragm show better performance. In addition, the synthesis process is simple and does not require the introduction of additional additives and equipment. It can be synthesized under existing conditions, indicating that the porous Na-β''-Al2O3 synthesized in the present invention has practical application potential.

[0123] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A porous sodium solid electrolyte powder, which is Na-β''-Al2O3, has a pore size of 5nm~100nm and a porosity of 50%~70%.

2. A method for preparing a porous sodium solid electrolyte powder, comprising the following steps: Mixing an aluminum source with sodium carbonate to obtain a powder; the aluminum source is selected from boehmite, α-Al2O3 or diaspore; The powder is placed in a heat-resistant and high-thermal-conductivity container for calcination to obtain a porous sodium solid electrolyte powder; The thickness of the powder in the heat-resistant and highly thermally conductive container is 10-15 cm, the calcination temperature is 1250° C.-1300° C., and the calcination time is 1 h-1.5 h.

3. The preparation method according to claim 2, characterized in that: The heating rate of the calcination is 5°C / min to 8°C / min.

4. The preparation method according to claim 3, characterized in that: The mass ratio of the aluminum source to sodium carbonate is 6.5-7:

1.

5. The preparation method according to claim 4, characterized in that: The heat-resistant and high-thermal-conductivity container is an alumina calcining sagger.

6. A diaphragm comprising a polymer diaphragm and a coating layer formed on at least one surface of the polymer diaphragm, wherein the coating layer comprises the porous sodium solid electrolyte powder according to claim 1 or the porous sodium solid electrolyte powder prepared by the method according to any one of claims 2 to 5.

7. The diaphragm according to claim 6, characterized in that The particle size of the porous sodium solid electrolyte powder is 400nm~600nm.

8. The diaphragm according to claim 7, characterized in that The coating layer also includes a binder and a wetting agent.

9. The diaphragm according to claim 8, characterized in that The binder is selected from at least one of carboxymethyl acrylate, polyvinylidene fluoride and its derivatives, carboxymethyl cellulose salt and polyacrylate; The wetting agent is selected from at least one of sodium lauryl sulfate and a condensate of fatty alcohol and ethylene oxide.

10. A sodium ion battery comprising the separator according to any one of claims 6 to 9.